PRAKTIK DHARMAYATRA DALAM MEMPERKUAT KEYAKINAN UMAT BUDDHA DI ERA MODERN - Edi Prasetiyo; Budi Utomo (Pascasarjana Universitas Hindu Indonesia, 2024)
The practice of Dharmayatra has long been an integral part of the Buddhist tradition. The aim of this study was to explore how Dharmayatra practices can strengthen Buddhist beliefs in the modern era. This research method is a literature study that involves the analysis and synthesis of relevant literature regarding Dharmayatra practices. The results showed that Dharmayatra practice helps Buddhists to increase their understanding of Buddhist teachings, increase their sense of connection with the Buddhist community, and strengthen their faith and commitment to Buddhist practice. This practice is also considered a means to overcome the challenges of modern life and gain inner peace. These findings suggest that Dharmayatra can be a relevant and beneficial practice for Buddhists in the modern era, and can assist them in living an authentic and meaningful Buddhist life despite some shortcomings in practicing it.